Transformasi Pendidikan Digital Mahasiswa FEB Universitas Dharma Andalas Saat Pandemi Covid 19 - Anna Marina; Nofri Yendra (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2022)
The purpose of the study was to determine the effect of the use of smartphones, online learning systems and the use of Moodle on the learning achievement of FEB students at Dharma Andalas University partially and simultaneously during the covid 19 pandemic. 284 people was determined by a sampling technique of 20% of the population. Data collection techniques with documentation and survey studies use primary data in the form of questionnaires and secondary data through library research. All research variables meet the instrument test and classical assumption test, the results of the regression equation Y = 72,479 + 0.739X1 + 0.256X2 + 0.437X3 + e. The results of the study show that the use of smartphones, online learning systems and the use of moodle have a significant positive effect on student achievement at a significance level of 5%. The correlation between the use of smartphones, online learning systems and the use of Moodle with moderate learning achievement is 0.683. The use of smartphones, online learning systems and the use of Moodle were able to explain the learning achievement of FEB students at Dharma Andalas University 0.517, the remaining 48.33 were explained by other variables not included in the research model. ABSTRAK Tujuan penelitian mengetahui pengaruh penggunaan smartphone, sistem pembelajaran daring dan penggunaan moodle terhadap prestasi belajar mahasiswa FEB Universitas Dharma Andalas secara parsial dan simultan saat pandemi covid 19. Populasi penelitian 1.132orang sampel 284 orang ditentukan dengan teknik pengambilan sampel 20% dari populasi. Teknik pengumpulan data dengan studi dokumentasi dan survei menggunakan data primer berupa angketdan data sekunder melalui library research. Semua variabel penelitian memenuhi uji instrumen danuji asumsi klasik, didapat hasil persamaan regresi Y = 72.479 + 0.739X1 + 0.256X2 + 0.437X3 + e. Hasil pengujian hipotesis secara parsial dan simultan menunjukkan penggunaansmartphone, sistem pembelajaran daringdan penggunaan moodleberpengaruh positif signifikan terhadap prestasi belajar mahasiswa FEB Universitas Dharma Andalas pada tingkat signifikansi 5%. Korelasi penggunaan smartphone, sistem pembelajaran daringdan penggunaan moodledengan prestasi belajar sedang 0.683. Penggunaan smartphone, sistem pembelajarandaringdan penggunaan moodlemampu menjelaskan prestasi belajar mahasiswa FEB Universitas Dharma Andalas 0.517 sisanya 48.33 dijelaskan oleh variabel lain tidak termasuk ke dalam model penelitian.